Post-Swim Facial Skin Hydration and Sebum Levels Among Young Adult Swimmers in Bandung: A Descriptive Cross Sectional Study - Zhillan Zhalila Prakoso; Sukmawati Tansil Tan (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: Instrument-based descriptions of facial skin condition after swimming are limited in Indonesian populations, but single post swim measurements cannot establish chlorine related effects. Objective: To describe post swim facial sebum and hydration categories among young adult swimmers in Bandung. Methods: A descriptive cross sectional study included 70 active swimmers aged 18–35 years at two public pools on April 25–26, 2024. Five facial sites were assessed once immediately after swimming using the Runve 45 Skin Analyzer following gentle micellar water cleansing. Data were summarized as frequencies and percentages; no inferential tests were performed. Results: Low sebum was most frequent on the nose (72.9%), right cheek (70.0%), and chin (62.9%). Dry hydration was most frequent on the nose (18.6%), right cheek (11.4%), and left cheek/chin (10.0% each). Conclusion: Low sebum and dry-skin categories were observed at several facial sites after swimming. Because no pre swim baseline, comparison group, measured chlorine concentration, or standardized post cleansing recovery interval was available, the findings should be interpreted descriptively rather than causally.